2000
DOI: 10.1038/79802
|View full text |Cite
|
Sign up to set email alerts
|

APRIL and TALL-1 and receptors BCMA and TACI: system for regulating humoral immunity

Abstract: We report that the tumor neurosis factor homolog APRIL (a proliferation-inducing ligand) stimulates in vitro proliferation of primary B and T cells and increases spleen weight due to accumulation of B cells in vivo. APRIL functions via binding to BCMA (B cell maturation antigen) and TACI (transmembrane activator and CAML-interactor) and competes with TALL-I (also called BLyS or BAFF) for receptor binding. Soluble BCMA and TACI specifically prevent binding of APRIL and block APRIL-stimulated proliferation of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
302
5
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(323 citation statements)
references
References 27 publications
13
302
5
1
Order By: Relevance
“…The data were consistent with previous reports (19,22,23) and showed that, over time, the primary anti-NP response was significantly reduced with BAFF inhibition when compared with control animals (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The data were consistent with previous reports (19,22,23) and showed that, over time, the primary anti-NP response was significantly reduced with BAFF inhibition when compared with control animals (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
“…4, right panel). These data are consistent with previously published reports using BAFF inhibitors (19,22).…”
Section: Baff Blockade Inhibits T-dependent Ab Responses Including Hsupporting
confidence: 83%
See 1 more Smart Citation
“…11 B cell-activating factor exerts its effect by binding to three known receptors: transmembrane activator and calcium modulator cyclophilin ligand interactor (TACI), B-cell maturation antigen (BCMA) and BAFF-receptor/BLyS receptor 3 (BAFF-R). 8,[12][13][14][15] BAFF-R and BCMA expression are restricted to B cells, whereas TACI is found on both B cells and activated T cells. BAFF receptors appear to be expressed on immunoglobulin-positive B cells but not on immunoglobulin-negative pre-and pro-B cells.…”
Section: Introductionmentioning
confidence: 99%
“…APRIL was shown to have a remarkable capacity to stimulate both solid and lymphoid tumor growth (21,22). Currently, 2 TNF receptor family members, TACI and BCMA, have been shown to bind to APRIL with high affinity (23).…”
mentioning
confidence: 99%